2004
DOI: 10.1074/jbc.m312120200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for the Catalytic and Hemopexin Domains of Membrane Type 1-Matrix Metalloproteinase in Substrate Degradation and Cell Migration

Abstract: Substrate degradation and cell migration are key steps in cancer metastasis. Membrane-type 1-matrix metalloproteinase (MT1-MMP) has been linked with these processes. Using the fluorescein isothiocyanate (FITC)-labeled fibronectin degradation assay combined with the phagokinetic cell migration assay, structurefunction relationships of MT1-MMP were studied. Our data indicate that MT1-MMP initiates substrate degradation and enhances cell migration; cell migration occurs as a concurrent but independent event. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 51 publications
5
82
0
Order By: Relevance
“…It has become clear that protease-independent migration strategies exist. Recently it was shown that catalytically inactive MT1-MMP mutant supported cell migration similarly to the wild type enzyme and the cell migration supporting activity was accounted for the catalytic domain and the Cterminal domain (Cao et al, 2004). Other investigators have similarly suggested a migration inducing ability of MMP-9 independent of the catalytic activity (Sanceau et al, 2003).…”
Section: Multiple Roles Of Proteinases In Cell Migration and Invasionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has become clear that protease-independent migration strategies exist. Recently it was shown that catalytically inactive MT1-MMP mutant supported cell migration similarly to the wild type enzyme and the cell migration supporting activity was accounted for the catalytic domain and the Cterminal domain (Cao et al, 2004). Other investigators have similarly suggested a migration inducing ability of MMP-9 independent of the catalytic activity (Sanceau et al, 2003).…”
Section: Multiple Roles Of Proteinases In Cell Migration and Invasionmentioning
confidence: 90%
“…Another point to note is that the proteinases have functions independent on their proteolytic activity. This has been well established with the uPA/uPAR system (Blasi and Carmeliet, 2002) and evidence is accumulating that the MMPs function similarily (Cao et al, 2004;Sanceau et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported motility to be somewhat enhanced by overexpression of wild-type MT1 (Gingras et al, 2001;Rozanov et al, 2001;Cao et al, 2004;Takino et al, 2004). MT1 effects on cell motility may be exerted through integrin activation, as MT1-mediated cleavage of the vitronectin receptor avb3 enhanced breast cancer cell motility on this substrate (Deryugina et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether MT1 also promoted the migration of ovarian cancer cells, as demonstrated in other cancer cell types (Gingras et al, 2001;Rozanov et al, 2001;Cao et al, 2004;Takino et al, 2004), the transfected cells were subjected to a transwell collagen migration assay. In contrast to its striking effect on collagen degradation, MT1 expression did not enhance cell migration ( Figure 4B).…”
Section: Membrane-type 1 Promotes Invasion Solely Through Enhanced Mamentioning
confidence: 99%
“…More recently, Takino et al [107] demonstrate that MT1-MMP-mediated MEK/ERK activation leads to tumor cell invasion in type-1 collagen gel. By using cDNAs encoding dominant negative inhibitors targeted to different signaling pathways, Rac 1 activation by MT1-MMP has also been involved in cell migration [108]. Processing of integrin α v subunit by MT1-MMP leads to tyrosine phosphorylation of focal adhesion kinase and cell migration [100].…”
Section: Mt-mmp Can Induce Intracellular Signal Transductionmentioning
confidence: 99%